PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE SYNERGETIC TEACHING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 30 PADANG TAHUN PELAJARAN 2012/2013 - Aprimadani, Aprimadani; K, Delsi; Cesaria, Anna (STKIP PGRI Sumbar, 2013)
This research based on the lack of comprehension of the mathematical concepts that looked from the study results of students grade VIII SMP 30 Padang. One of the way to increase students comprehension of mathematical concepts is with implement an active learning strategy type synergetic Teaching. This study aims to determine whether students comprehension of mathematical concepts by applying active learning strategies type Synergetic Teaching is better than the students comprehension of mathematical concepts with conventional learning in grade VIII SMP 30 Padang. This type of research is experimental research on the subject with a random design. The population in this study were all of the students grade VIII in the academic year 2012/2013. The sample in this study is VIII.7 class as the experimental class and the VIII.8 as the control class. Research instruments is an essay test with a reliability of 0.87. Based on the analysis of the data found that the two classes are normally distributed and homogeneous samples at the level of Î± = 0.05 and hypothesis test results obtained from the P-value = 0.008, less than Î± = 0.05, then the hypothesis in this research received. Thus, it can be concluded that the students comprehension of mathematical concepts by applying active learning strategies type synergetic Teaching better than students comprehension of mathematical concepts with conventional learning in class VIII SMP 30 Padang.